NRF-1 genotypes and endurance exercise capacity in young Chinese men. Issue 5 (9th January 2008) - He, Z; Hu, Y; Feng, L; Li, Y; Liu, G; Xi, Y; Wen, L; Lucia, A
Abstract : Background: Nuclear respiratory factor 1 (NRF-1) is a critical component of the energy-sensing mechanism in mammalian cells, and translates physiological signals (particularly those induced by exercise) into increased capacity for mitochondrial biogenesis and oxidative phosphorylation. Objective: To study the possible association between rs2402970, rs6949152 and rs10500120 NRF-1 genotypes and several phenotypes indicative of maximum (VO2max ) and submaximum aerobic capacity (ventilatory threshold (VT) and metabolic cost of submaximum running at 12 km/hour (running economy; RE)) both at baseline and in response to a 18-week endurance training programme in young Chinese men of Han origin (n = 102; 19 (SD 1) years). Results: For rs2402970, a significant genotype effect was seen for VT (p = 0.004) and RE (p = 0.027). For rs6949152, a significant interaction (genotype×training) effect (p = 0.047) was found for VT. Conclusions: There is an association between NRF-1 genotypes (rs2402970 and rs6949152 polymorphisms) and the baseline and/or training response of human aerobic capacity. More research is needed to corroborate our data in other ethnic groups with lower fitness levels at the pre-training state (particularly Caucasians) and to identify the molecular mechanisms involved in the genotype–phenotype associations we found.